Child wasting is a severe public health problem in the predominantly rural population of Ethiopia: A community based cross-sectional study - Amare Tariku; Gashaw Andargie Bikis; Haile Woldie; Molla Mesele Wassie; Abebaw Gebeyehu Worku (BMC, 2017)
Abstract Background In Ethiopia, child wasting has remained a public health problem for a decade's, suggesting the need to further monitoring of the problem. Hence, this study aimed at assessing the prevalence of wasting and associated factors among children aged 6-59 months at Dabat District, northwest Ethiopia. Methods A Community based cross-sectional study was undertaken from May to June, 2015, in Dabat District, northwest Ethiopia. A total of 1184 children aged under five years and their mothers/caretakers were included in the study. An interviewer-administered, pre-tested, and structured questionnaire was used to collect data. Standardized anthropometric body measurements were employed to assess the height and weight of the participants. Anthropometric body measurements were analyzed by the WHO Anthro Plus software version 1.0.4. Wasting was defined as having a weight-for-height of Z-score lower than two standard deviations (WHZ < −2 SD) compared to the WHO reference population of the same age and sex group. In the binary logistic regression, both bivariate and multivariate analyses were done to list out factors associated with wasting. All variables with P-values of < 0.2 in the bivariate analysis were earmarked for the multivariate analysis. Both Crude Odds Ratio (COR) and Adjusted Odds Ratio (AOR) at 95% Confidence Interval (CI) were computed to determine the strength of association. In the multivariate analysis, variables at P-values of < 0.05 were identified as determinants of wasting. Results The overall prevalence of wasting was 18.2%; 10.3% and 7.9% of the children were moderately and severely wasted, respectively. Poor dietary diversity [AOR = 2.08, 95% CI: 1.53, 4.46], late initiation of breastfeeding [AOR = 1.43, 95% CI: 1.04, 1.95], no postnatal vitamin-A supplementation [AOR = 1.55, 95% CI: 1.04, 2.30], and maternal occupational status [AOR = 2.31, 95% CI: 1.56, 3.42] were independently associated with wasting in the study area. Conclusion Wasting is a severe public health problem in Dabat District. Therefore, there is a need to strengthen the implementation of optimal breastfeeding practice and dietary diversity. In addition, improving the coverage of mothers' postnatal vitamin-A supplementation is essential to address the burden of child wasting.